The Intricacies of Polypharmacy and Drug Interactions in Schizophrenia Treatment - Dwivedi, Jyotsana; Seemab, Mohd.; Wal, Pranay; Dey, Piyali; Rathinam, Thirumalaikumaran; Dhamini, Avula; Khan, Abida (Current Drug Metabolism, 2025)
IntroductionPolypharmacy is frequently practiced in the management of schizophrenia due to its chronic nature, recurrent relapses, and associated comorbidities. While combining psychotropic medications may benefit patients with treatment-resistant symptoms, it poses risks such as drug–drug interactions (DDIs), adverse effects, and reduced medication adherence. The absence of uniform prescribing standards further complicates clinical decision-making.MethodsThis narrative review was conducted using a scoping methodology. Databases including PubMed, Scopus, and Web of Science were searched for English-language publications from 2000 to 2024. Search terms included “schizophrenia,” “polypharmacy,” “drug–drug interactions,” “clinical outcomes,” and “pharmacogenetics.” Eligible sources included clinical trials, observational studies, systematic reviews, and treatment guidelines. Exclusion criteria were non-English articles, gray literature, and individual case reports.ResultsPolypharmacy is reported in 30–60% of individuals with schizophrenia, especially in institutionalized or treatment-resistant populations. Treatment regimens often involve multiple antipsychotics along with adjunctive antidepressants or mood stabilizers. This approach is associated with increased risks of metabolic syndrome, cardiovascular events (e.g., QT prolongation), extrapyramidal symptoms, and decreased adherence. Interindividual variability in pharmacogenetics further affects drug efficacy and safety. Innovative approaches like genotype-guided therapy and computerized clinical decision-support systems are promising but not yet widely implemented.DiscussionAlthough polypharmacy may offer symptomatic relief in specific scenarios, it requires careful management due to its potential to cause harm. Rational prescribing, close monitoring, and attention to individual patient factors such as pharmacogenetic profiles are essential to optimize therapy.ConclusionEnsuring a balance between therapeutic benefit and adverse effects is crucial when employing polypharmacy in schizophrenia treatment. Integrating personalized medicine strategies, regular monitoring, and deprescribing practices when feasible can enhance clinical outcomes and patient safety.
Keywords: clinicaloutcomes